Factors influencing access to safe drinking water and sanitation in Northeast India: evidence from National Family Health Survey (NFHS-5) - Christopher Tirkey; Rajiv Gurung; Runa Rai; Kishore Kumar Takri (International Journal of Social Economics, 2025)
Purpose Universal access to safe drinking water and sanitation facilities as recognized in the Sustainable Development Goals, is an essential human right. However, geographical disparities have led to extremely limited provisions of improved drinking water and sanitation facilities across states. Despite several policy interventions, the Indian states are still struggling to achieve their targets. This paper attempts to explore the factors influencing access to improved drinking water and sanitation in India’s Northeastern state of Assam. Design/methodology/approach This study makes a state-level investigation by solely relying on a nationally representative cross-sectional dataset, that is, the National Family Health Survey (NFHS-5) dataset. Descriptive statistics and logistic regression was used to analyze the data. Findings The key determinants that influence access to improved drinking water include education, wealth, place of residence, marital status, type of house and household structure. Likewise, the variables influencing households’ access to improved sanitation facilities include gender, education, household wealth, place of residence and house type, ownership of mobile phones. Practical implications The findings suggest increased public investment aimed toward infrastructure development for WASH facilities and the provision of drinking water and sanitation services at subsidized rates. Originality/value This study is the first of its kind in Northeast India. A state-level investigation solely relying on a nationally representative cross-sectional dataset has not been conducted yet. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-03-2025-0228